Referent selection in children with Autism Spectrum Condition and intellectual disabilities: Do social cues affect word-to-object or word-to-location mappings?. (August 2019) - Field, Charlotte; Lewis, Charlie; Allen, Melissa L.
Highlights: This study involved a speaker gazing and/or pointing at a novel object. Children with Autism Spectrum Condition encode object names from gaze and pointing. For gaze, this ability relates to chronological age. Children with intellectual disabilities do not fast map from 'referential pointing'. Object positioning affects fast mapping in children with intellectual disabilities. Abstract: Background: There is conflicting evidence regarding whether children with Autism Spectrum Condition (ASC) and intellectual disabilities (ID) follow social pragmatic cues such as a speaker's eye gaze or pointing towards a novel object to assist mapping a new word onto a new object (e.g. fast mapping). Aims: We test fast mapping from a speaker's gaze and pointing towards objects in children with ASC and ID with varying chronological and receptive language ages compared with receptive language matched groups of typically developing (TD) children. Methods and Procedure: Across eight trials, a speaker gazed and/or pointed towards one out of two objects while saying a new word. Pointing was either 'referential' (with intention), or 'incidental' (without obvious intention). To investigate whether children formed more robust word-to-object links rather than associative word-to-location ones, we reversed the original location of the objects in half of the test trials. Outcomes and Results: Children with ASC were as successful as TD children using social cues to form word-to-object mappings. Surprisingly, children with ID did not fast map from referential pointing, or when objects changed location. Conclusions and Implications: Children with ID may use different processes to facilitate word learning compared to TD children and even children with ASC.